Comparison of six assessment tools to screen for obstructive sleep apnea in patients with hypertension. Issue 11 (14th September 2021) - Zheng, Zhenzhen; Sun, Xishi; Chen, Riken; Lei, Wei; Peng, Min; Li, Xiongbin; Zhang, Nuofu; Cheng, Junfen
Abstract: Background: Obstructive sleep apnea (OSA) is often accompanied by other complications, especially hypertension. Hypothesis: The purpose of this study is to compare the application value of six tools in the screening of OSA in patients with hypertension. Compared with other questionnaires, we hypothesized that Berlin performed better in screening hypertensive patients suspected of OSA. Methods: In this study, we collected the basic data and polysomnography (PSG) data of patients diagnosed with hypertension who underwent PSG at the Sleep Medicine Center of the First Affiliated Hospital of Guangzhou Medical University from April 2012 to March 2021. The sensitivity, specificity, positive predictive value, negative predictive value, area under the curv (AUC) and diagnostic odds ratio (DOR) of the six screening tools were then calculated, and their correlation with the sleep apnea hypopnea index (AHI) analyzed. Results: There were 303 males (303/398, 76.1%) out of 398 hypertension patients suspected of OSA. The area under the curve of the Berlin questionnaire's receiver operating characteristic (ROC) curve reached 0.753 (95%CI: 0.707–0.794). When the AHI was 5, 15 and 30 times/h as the cut‐off points, the sensitivity and negative predictive value of Berlin were the highest at 0.947 and 0.630, 0.970 and 0.851, and 0.988 and 0.957 respectively, while the specificity and positive predictive value of the Epworth Sleepiness Scale (ESS) were the highest at 0.696 and 0.729, 0.750 and 0.887, and 0.674 and 0.575 respectively. The DOR value of the Berlin questionnaire could reach 18.333 when the AHI cut‐off point was 30 times/h. Berlin had the largest rank correlation coefficient with AHI at 0.466. Conclusion: The Berlin questionnaire can be considered a priority for the screening and stratifying of hypertensive patients suspected of OSA.